Խեթերեն marnuwa բառը - Հմայակյան, Հասմիկ (Ասողիկ հրատ.)
The author attempts to etymologize Hittite marnuwa from I-Е *mer-, *mor- (meaning blacken, dark color) that entomologically relates to I-Е reconstructed stem *moro for black mulbeny or black raspberry. The author supposes that marnuwa found in Hittite texts is an alcoholic drink having ritual evil preventing function and probably was prepared from black mulberry or black raspberry. It should be remembered that in 1-Е languages names for these different plants always has been mixed.
Keywords: Լեզվաբանություն